Human subjectivity in the prenatal period - Biesaga, Tadeusz (Studia Ecologiae et Bioethicae, 2020)
The article rejects various attempts to negate the subjectivity of human embryo, formulated among others in the Polish debate entitled 'Stem cells - life for life?' and organised by the Ministry of Scientific Research and Information Technology in 2003 and 2004. The Author thinks that the proposal to treat a human embryo as a deceased donor of organs, is wrong both in the field of embryology and philosophical anthropology. It is also wrong to question the subjectivity of human embryo using various criteria of growth (developed nervous system, brain, consciousness, participation in the life of society and looking after one's own interests). For these criteria do not define humanity but describe human being in various phases of expressions of his/her human nature. That is why it is not acceptable to make the right to life conditional on the stage and degree of the actualization of humanity. Furthermore, one cannot justify the deprivation of the subjectivity of human embryo because of medical progress and the so-called good of humankind. The acceleration of progress cannot be done at the cost of life of some group of human beings.